Validating the Job Stress Scale for Indonesian Police: A CFA Study - Karin Hadiyanti; Erita Yuliasesti Diah Sari (Jurnal Psikologi Teori dan Terapan, 2025)
Background: Indonesian adaptation of job stress scale have been tested on teacher samples, re-testing and re-measuring validity and reliability are necessary for use with police samples. Conducting confirmatory factor analysis (CFA) on the Indonesian job stress scale for police samples is critically important because policing is a highly stressful occupation with unique demands not found in teaching professions. Objective: This study aims to measure the validity and reliability of the Indonesian adapted Job Stress Scale for Indonesian police personnel. Method: Using a cross-sectional design, data were collected from a population of 121 Satsamapta officers at Polresta Yogyakarta through accidental sampling, yielding 86 complete responses. CFA evaluated construct validity, while Cronbach’s alpha assessed the reliability of the 13-item Job Stress Scale comprising two factors. Results: Three items (8, 9, and 10) were invalid (factor loading < 0.5). After removal, model fit indices improved significantly (CFI = 0.989, TLI = 0.984, SRMR = 0.0322, RMSEA = 0.0690), and reliability increased to 0.967. Conclusion: The adapted scale, with 10 items, is valid and reliable for measuring work stress among police personnel in Indonesia. This tool can aid further research and interventions to address work stress in law enforcement.